Waste Factors Analysis in Instant Noodle Production Process at PT Prakarsa Alam Segar Bekasi: A Lean Six Sigma Approach - Resista Vikaliana; Prayogi Aditama; Eman Sulaeman Nasim; Irwansyah Supandi (Universitas Mercu Buana, 2022)
PT Prakarsa Alam Segar is one of the largest noodle-making companies in Indonesia. In its production activities, waste is one of the main problems of PT Prakarsa Alam Segar. This study aims to determine the activities that result in waste and the right solution to minimize waste during the production process. This study focuses on the use of flour raw materials in the production process in the Noodle 2 department. This research is a descriptive qualitative research conducted using the Lean Six Sigma (LSS) approach with the DMAIC (Define, Measure, Analyze, Improve, and Control) method, a framework to fix problematic processes. The analysis techniques used included cause-effect diagrams, SIPOC diagrams, and FMEA. The results showed that the failure and waste of flour material during the instant noodle production process in the Noodle 2 department was related to 3 processes on the production line, namely: (1) Roll Press, (2) Cutting, and (3) Frying.